Hyperoside attenuates osteoarthritis progression by targeting PI3K/Akt/NF-κB signaling pathway: In vitro and in vivo studies - Yang Yang; Jia-Jie Huang; Gao-Sheng Zhu; Wei Hu (Journal of Functional Foods, 2022)
Osteoarthritis (OA) is a chronic and progressive degenerative disease, and the main characteristic is destruction of articular cartilage. Hyperoside, a type of active flavonoid compound, has been verified valid for anti-inflammation. Nevertheless, whether hyperoside has positive effects on OA development remains unclear. Thus current research was conducted to explore the protective role of hyperoside in the development of OA and its potential molecular mechanism through in vitro and in vivo research. In vitro, excessive secretion of pro-inflammatory mediators including, prostaglandin E2 (PGE2), nitric oxide (NO), interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-α), inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) was induced by interleukin -1β (IL-1β), which could be significantly reversed by the pretreatment of hyperoside and the effect was dose dependent. Moreover, hyperoside suppressed IL-1β-mediated extracellular matrix (ECM) damage. Mechanistically, hyperoside potently restrained IL-1β-mediated phosphorylation level of PI3K/Akt, as well as NF-κB pathway activation. Furthermore, molecular docking research revealed strong binding ability between hyperoside and PI3K. Destabilization of the medial meniscus (DMM) mice model was implemented to clarify the hyperoside-mediated therapeutic effect in cartilage degeneration and pain symptom in vivo. In conclusion, these results provide potent evidence that hyperoside could be used as a promising treatment strategy for the suppression during OA progress.